Structure of Escherichia coli tryptophanase purified from an alkaline‐stressed bacterial culture. Issue 11 (1st November 2015) - Rety, Stephane; Deschamps, Patrick; Leulliot, Nicolas
Abstract : Tryptophanase is a bacterial enzyme involved in the degradation of tryptophan to indole, pyruvate and ammonia, which are compounds that are essential for bacterial survival. Tryptophanase is often overexpressed in stressed cultures. Large amounts of endogenous tryptophanase were purified from Escherichia coli BL21 strain overexpressing another recombinant protein. Tryptophanase was crystallized in space group P 65 22 in the apo form without pyridoxal 5′‐phosphate bound in the active site.